3D Printing of Octacalcium Phosphate Bone Substitutes - Komlev, Vladimir S.; Popov, Vladimir K.; Mironov, Anton V.; Fedotov, Alexander Yu.; Teterina, Anastasia Yu.; Smirnov, Igor V.; Bozo, Ilya Y.; Rybko, Vera A.; Deev, Roman V. (Frontiers in Bioengineering and Biotechnology, 2015)
Biocompatible calcium phosphate ceramic grafts are able of supporting new bone formation in appropriate environment. The major limitation of these materials usage for medical implants is the absence of accessible methods for their patient-specific fabrication. 3D printing methodology is an excellent approach to overcome the limitation supporting effective and fast fabrication of individual complex bone substitutes. Here we proposed a relatively simple route for 3D printing of octacalcium phosphates in complexly shaped structures by the combination of inkjet printing with post-treatment methodology. The printed octacalcium phosphate blocks were further implanted in the developed cranial bone defect followed by histological evaluation. The obtained result confirmed the potential of the developed octacalcium phosphates bone substitutes, which allowed 2.5-time reducing of defect’s diameter at 6.5 months in a region where native bone repair is extremely inefficient.